A novel cDNA‐uPA/SCID/Rag2−/−/Jak3−/− mouse model for hepatitis virus infection and reconstruction of human immune system. Issue 3 (12th January 2023) - Uchida, Takuro; Teraoka, Yuji; Imamura, Michio; Abe‐Chayama, Hiromi; Makokha, Grace Naswa; Hayes, Clair Nelson; Aikata, Hiroshi; Hamamura, Satoko; Ishida, Yuji; Tateno, Chise; Shirouzu, Takayuki; Kawai, Shintaro; et al.
Abstract: Although human hepatocyte‐transplanted immunodeficient mice support infection with hepatitis viruses, these mice fail to develop viral hepatitis due to the lack of an adaptive immune system. In this study, we generated new immunodeficiency cDNA‐urokinase‐type plasminogen activator (uPA)/SCID/Rag2 −/− /Jak3 −/− mice and established a mouse model with both a humanized liver and immune system. Transplantation of human hepatocytes with human leukocyte antigen (HLA)‐A24 resulted in establishment of a highly replaced liver in cDNA‐uPA/SCID/Rag2 −/− /Jak3 −/− mice. These mice were successfully infected with hepatitis B virus (HBV) and hepatitis C virus (HCV) for a prolonged period and facilitate analysis of the effect of anti‐HCV drugs. Administration of peripheral blood mononuclear cells (PBMCs) obtained from an HLA‐A24 donor resulted in establishment of 22.6%–81.3% human CD45‐positive mononuclear cell chimerism in liver‐infiltrating cells without causing graft‐versus‐host disease in cDNA‐uPA/SCID/Rag2 −/− /Jak3 −/− mice without human hepatocyte transplantation. When mice were transplanted with human hepatocytes and then administered HLA‐A24‐positive human PBMCs, an alloimmune response between transplanted human hepatocytes and PBMCs occurred, with production of transplanted hepatocyte‐specific anti‐HLA antibody. In conclusion, we succeeded in establishing a humanized liver/immune system characterized by an allo‐reaction between transplanted human immune cells and human liver using a novel cDNA‐uPA/SCID/Rag2 −/− /Jak3 −/− mouse. This mouse model can be used to generate a chronic hepatitis mouse model with a human immune system with application not only to hepatitis virus virology but also to investigation of the pathology of post‐transplantation liver rejection.